Aplikasi Sistem Informasi Penerapan Vogel's Approximation Method (VAM) Untuk Meminimalkan Biaya Transportasi Pengiriman Barang (Study Kasus : JNE Cab. Utama Medan) - Setiawan Setiawan; Olven Manahan (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2020)
In the distribution process, a large number of transportation costs are required because the costs incurred are unstable and also depend on field and weather conditions. In addition, the road conditions in Medan are getting congested, so that traffic jams have to be dealt with by the delivery party. Therefore a strategy is needed to minimize costs so that problems do not arise in distributing products to various regions. The information system that will be built to help resolve cases that occur in service providers, especially at the JNE Medan Main Branch, uses a method known as a method of transportation. Vogel's Approximation Methods (VAM) is a transportation method used to regulate the distribution from sources that provide the same product to places where it is optimally needed.